Caracterização ambiental e avaliação dos serviços ecossistêmicos de manguezais para as áreas portuárias de São Luís, Maranhão, Brasil - RIBEIRO, Suellen Pinheiro (2025)
Ecosystem goods and services provide both direct and indirect benefits for sustaining life and enhancing human well-being. Mangroves fulfill essential environmental and social functions, including carbon sequestration, coastal protection, increased fish stocks, tourism, education, and cultural preservation. However, deforestation and urban-industrial development threaten their ability to provide these services. This study aimed to analyze the ecosystem services of mangroves in port areas, focusing on conservation, sustainable management, and the enhancement of these ecosystems. An interdisciplinary approach was adopted, combining a systematic literature review, identification, quantification, and valuation of mangrove ecosystem services based on the Common International Classification of Ecosystem Services (CICES). Additionally, surveys were conducted to assess community perceptions of the importance of these ecosystems and their willingness to pay for conservation efforts. The research was structured into three chapters: (i) a systematic literature review, (ii) an analysis of geodiversity and ecosystem services of mangroves in the port complex, and (iii) a socio environmental perception study and an economic-ecological valuation in the Mangue Seco (Raposa) community. The first chapter, based on a systematic review of 28 publications from 2006 to 2023, highlighted the limited number of studies on mangroves in port areas. Most of the research focused on regulatory services, followed by provisioning, support, and cultural services. The predominance of studies conducted in China suggests a concentration in economically developed port regions, emphasizing the need for a more balanced global distribution of research on this topic. The second chapter consisted of an exploratory and qualitative analysis of three areas: the Port of Itaqui, the Camboa dos Frades Community, and the Mangue Seco Community. The results indicated that mangroves are essential for local communities, particularly in Camboa dos Frades and Mangue Seco, whereas the Port of Itaqui exhibited a lower supply of ecosystem services due to port activities. The third chapter revealed that 93% of the Mangue Seco community is willing to contribute financially to mangrove conservation. In conclusion, mangroves play a vital role in improving the quality of life of local communities and in conserving biodiversity. Therefore, it is essential to implement effective management and conservation strategies to mitigate the impacts of port activities and ensure the long-term sustainability of mangroves and the ecosystem services they provide.